2009
DOI: 10.1111/j.1365-3016.2009.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Do women change their health behaviours in pregnancy? Findings from the Southampton Women's Survey

Abstract: A woman's life style choices before and during pregnancy have important implications for her unborn child, but information on behaviour can be unreliable when data are collected retrospectively. In particular there are no large longitudinal datasets that include information collected prospectively before pregnancy to allow accurate description of changes in behaviour into pregnancy. The Southampton Women's Survey is a longitudinal study of women in Southampton, UK, characterised when they were not pregnant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
195
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(235 citation statements)
references
References 14 publications
30
195
3
Order By: Relevance
“…A decrease in the consumption of alcohol from prepregnancy to early pregnancy has been reported across many populations (14,15,30,38) , but not all studies have reported the same level of abstinence during pregnancy as the women in the present study (30,32,38) . The toxic effects of alcohol on the fetus have been known for more than 40 years (39) and consumption of alcohol during pregnancy is associated with congenital birth defects (23,40) as well as unfavourable developmental (20) and neurological outcomes (16) .…”
Section: Alcoholcontrasting
confidence: 56%
See 1 more Smart Citation
“…A decrease in the consumption of alcohol from prepregnancy to early pregnancy has been reported across many populations (14,15,30,38) , but not all studies have reported the same level of abstinence during pregnancy as the women in the present study (30,32,38) . The toxic effects of alcohol on the fetus have been known for more than 40 years (39) and consumption of alcohol during pregnancy is associated with congenital birth defects (23,40) as well as unfavourable developmental (20) and neurological outcomes (16) .…”
Section: Alcoholcontrasting
confidence: 56%
“…An increase in milk consumption from pre-pregnancy to pregnancy has also been found in other populations (15,(30)(31)(32) . However, a British prospective study reported stable consumption of milk from pre-pregnancy to early pregnancy (28,38) . Early pregnancy is a time period where women are highly motivated to adopt a healthier lifestyle, including healthier beverage consumption habits.…”
Section: Milkmentioning
confidence: 99%
“…Six articles reported data on fruit and vegetable intake with inconsistent findings (Cuco et al, 2006a;Pinto et al, 2008;Crozier et al, 2009a;Crozier et al, 2009b;Paulik et al, 2009;Smedley et al, 2014). Paulik et al (2009) reported an increase in the percentage of women consuming both fruits and vegetables (more than 4 times per week) in pregnancy (85.7% vs 94.8% fruit and 67.6% vs 75.4% vegetables).…”
Section: Food Groups -Fruits and Vegetablesmentioning
confidence: 99%
“…Five articles reported data on beverage intake and the results varied greatly between studies (Hellerstedt et al, 1998;Cuco et al 2006a;Pinto et al, 2008;Crozier et al, 2009b;Skreden et al, 2014). Coffee and tea was the most commonly reported beverage, and consumption was found to decrease from before to during pregnancy in four studies (Hellerstedt et al, 1998;Pinto et al, 2008;Crozier et al, 2009b;Skreden et al, 2014).…”
Section: Beveragesmentioning
confidence: 99%
“…Pregnant women usually are very aware of the potential risks for their unborn child [144] and are correspondingly open to changes which would positively affect the health of their unborn child. The majority of pregnant women are prepared to reduce the amount of nicotine and/or alcohol they consume or even to stop smoking or drinking completely and are prepared to eat a healthy diet [145]. Nevertheless, a considerable percentage of pregnant women continue to display health-damaging behaviors, although the data on the incidence of this risky behavior, particularly with respect to nicotine and alcohol consumption in pregnancy, varies considerably depending on the country where the data was collected (cf.…”
mentioning
confidence: 99%